HUBUNGAN HYGIENE SANITASI DENGAN KUALITAS AIR MINUM SECARA MIKROBIOLOGIS PADA DAM DI KECAMATAN BANJARNEGARA TAHUN 2023 - Dwi Atin Faidah; Joko Malis Sunarno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
The global population using basic drinking water services increased by 1.7 billion people per year from 2000-2017. Drinking Water Depot (DAM) is a household business that supplies drinking water which is currently consumed by many people in Banjarnegara. In general, the quality of drinking water according to microbiological parameters should not contain Coliform bacteria such as E. coli. The aim of this research is to determine the relationship between sanitation hygiene and the microbiological quality of drinking water in DAM in Banjarnegara District in 2023. This research is an observational study using a cross sectional research design. The population in this study was all DAM in Banjarnegara District. This research used a total sampling of 27 DAMs that were operating at the time this research was conducted. The results of the research show that the sanitation picture mostly meets the requirements, the condition of the equipment all meets the requirements, personal hygiene mostly meets the requirements, the source of raw water is mostly from dug wells with the raw water quality mostly not meeting the requirements and the microbiological quality of the produced water mostly not meeting the requirements. requirements for Coliform parameters, but on further examination E. Coli mostly met the requirements. These results show that there is still a need to control processing so that DAM production results are suitable for public consumption. Routine monitoring by the relevant agencies needs to be tightened so that the quality of drinking water produced by DAM is maintained.